ANALISIS PENGARUH TINGKAT INFLASI, PENDAPATAN GADAI, HARGA EMAS, DAN PAJAK PENGHASILAN TERHADAP PENYALURAN KREDIT PT. PEGADAIAN (PERSERO) INDONESIA - Muhammad Ali Murtadho; Jeni Susyanti; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACTThis study aims to analyze the influence of variables rate inflation, lien income,gold prices, and income tax on the distribution of mortgage loans PT. Pawnshop(Persero) Indonesia. Hypothesis testing using multiple linear regression analysis,normality test and classical assumption test. The data used is time series data thatis the period 2009-2016. Based on the result of partial analysis of inflation rate(Sig. T equal to 0,104), pawn income (Sig. T sebesasr 0,188), and income tax (Sig.T equal to 0,551) have negative and insignificant effect to mortgage credit. whilegold price (Sig. t equal to 0,040) have a positive and significant effect to thedistribution of mortgage credit. Simultaneously all independent variables affectthe distribution of mortgage loans with Sig value. F of 002.Keywords: mortgage lending, inflation rate, lien income, gold price, income tax,and multiple linear regression.